Foreign institutional investors and the great productivity slowdown - Jan Philip Schain (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
This article analyzes the impact of institutional investors on firm productivity duringthe financial crisis 2008/09 across European manufacturing industries. Using propen-sity score matching combined with a difference in differences estimator I find a positivesignificant effect of 2% of foreign institutional ownership. Employing a variety of prox-ies for financial constraints, the article shows that the effect is driven by industries,countries, and firms that are more financially constrained indicating that foreign insti-tutional ownership prevents the known productivity slowdown during the financial crisisby alleviating financial constraints.
Keywords: F61; G23; G32; G01; L25; D22; D24; 330; Institutional Investors; Financial Crisis; Productivity; Financial Constraints